Stock Market Responses to Macroeconomic Dynamics: Testing for Long-Run Equilibrium in Nepal (Pravaha, 2018)
This study empirically examines the macro-economic factors of the stock market performance in Nepal. It considers the annual data of four macroeconomic variables; real GDP, inflation, interest rate and broad money supply from 1994 to 2016 and attempts to reveal the relative influence of these variables on stock prices represented by ‘NEPSE Index’ of the Nepalese capital market. Empirical results reveal that the performance of stock market is found to respond positively to real GDP, inflation and money supply, and negatively to interest rate. More importantly, cointegrating evidence cannot be found between macroeconomic variables and stock market index which suggests that stock price movements in Nepal are not explained by the macroeconomic variables. It supports random walk hypothesis in Nepalese stock market.Pravaha Vol. 24, No. 1, 2018, Page: 64-82